Optimalisasi Capaian Kinerja Organisasi Dengan Pemanfaatan Sistem Penatausahaan Barang Persediaan: Studi di Dinas Pekerjaan Umum Perumahan Dan Kawasan Permukiman Kota Yogyakarta - Fitri Yuliani (CV. ULIL ALBAB CORP, 2024)
Assets are items that are considered valuable by anyone and whatever their form, under the control of state assets, they are not just recorded on the balance sheet and then left there, but must provide benefits to the state, especially to the community because these assets must be able to bring prosperity to the people. This shows that the government is always committed and strives to ensure that state assets always provide benefits to the state. The more optimal the management of state assets, the more it will contribute to reducing financing for state assets because this optimization has an impact on the efficiency of maintenance spending and capital spending. State assets are held and used to support the implementation of the duties and functions of Ministries/Agencies. Therefore, it is necessary to optimize state assets that are not yet optimal in carrying out their duties and functions, so that they can provide economic and/or social benefits for the state to support the welfare of the people.